Doxologie, glasul IV antifon - Mocanu, Daniel (Yearbook (“Babes-Bolyai” University Cluj-Napoca. Faculty of Orthodox Theology), 2023)
The Great Doxology, mode IV. The Great Doxology, Glory to God in the highest, sung on Sundays and Holy Feasts at the Matins service, is an important hymn, in the morning service. Singing it in a solemn way, the liturgical community prepares for entering in the Holy Liturgy. In Transylvanian musical tradition, the most sung melodic version of the Great Doxology is the one on the 4th mode, on the antiphon form. The present melodic version, written in the Transylvanian manner, brings together the most used melodic formulas of the 4th mode, which we find in the oral musical tradition. By putting this composition into the liturgical circuit, we want to standardize the manner of singing the Great Doxology and offer an accessible musical version, with a medium degree of difficulty, with a church melodic line designed to satisfy the aesthetic tastes of the faithful.